2023
DOI: 10.1038/s41522-023-00386-4
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting modulates the intestinal microbiota and improves obesity and host energy metabolism

Abstract: Intermittent fasting (IF) is a promising paradigm for weight loss which has been shown to modulate the gut microbiota based on 16S rRNA gene amplicon sequencing. Here, 72 Chinese volunteers with a wide range of body mass index (BMI) participated in a three-week IF program during which an average loss of 3.67 kg body weight accompanied with improved clinical parameters was observed irrespective of initial anthropometric and gut microbiota status. Fecal samples were collected before and after the intervention an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In addition to that, the anticancer medications covered in the existing literature are all IV chemotherapies, while, in this review, we present orally administered targeted agents that rely on multiple factors for their bioavailability. These factors could include administration with respect to food (e.g., venetoclax [ 60 ]) and the gut microbiota that is altered by IF [ 20 , 74 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In addition to that, the anticancer medications covered in the existing literature are all IV chemotherapies, while, in this review, we present orally administered targeted agents that rely on multiple factors for their bioavailability. These factors could include administration with respect to food (e.g., venetoclax [ 60 ]) and the gut microbiota that is altered by IF [ 20 , 74 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The results published by Hu et al have shown that intermittent fasting generates changes in the microbiota by increasing the number of bacteroides and parabacteroides, which are known to be involved in beneficial effects on health [ 29 ]. In addition, enrichment of GABA-producing P. distasonis and B. thetaiotaomicron was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that supplementation of dietary Zn(ii)-curcumin (ZnCM) can attenuate gut dysbiosis during DOX-induced cardiomyopathy in vivo [ 140 ]. Furthermore, recent investigation has indicated that intermittent fasting (IF) has the potential to modulate the composition of gut microbiota, contributing to improvements in obesity and host energy metabolism [ 141 ]. Interestingly, a recent significant study found that alternate-day fasting (ADF) can aggravate DIC through transcription factor EB (TFEB)-mediated autophagy [ 41 ].…”
Section: The Potential Interventions Of Microbiota-targeted Therapeut...mentioning
confidence: 99%